Cooperation and conflict between women in the family. Issue 5 (24th October 2013) - Mace, Ruth
<x xml:space="preserve">Abstract</x> Here I review recent research on reproductive conflict between females in families and how it influences their reproductive behaviour. Kin selection can favor cooperation between parent and offspring, siblings, or unrelated co‐residents who share interests in other family members such as grand‐offspring. However, these are also the individuals most likely to be sharing resources, and so conflict can also emerge. While substantial interest has arisen in evolutionary anthropology, especially over the last two decades, in the possibility of cooperative breeding in humans, less attention has been paid to reproductive conflict among female kin. Communal breeding in animals is generally understood as emerging from competition over the resources needed to breed. Competition for household resources is a problem that also faces human families. Models suggest that in some circumstances, inclusive fitness can be maximized by sharing reproduction rather than harming relatives by fighting with them, even if the shares that emerge are not equal. Thus, competition and cooperation turn out to be strongly related to each other. Reproductive competition within and between families may have underpinned the biological evolution of fertility patterns (such as menopause) and the cultural evolution of marriage, residence, and inheritance norms (such as late male marriage or primogeniture), which can enhance cooperation and minimize the observed incidence of such conflicts.